Lesotho Government Property Asset Management - The case of civil Servants Housing Dwellings - Maboee, Thabiso (My University, 2006)
The government of Lesotho is experiencing a rapid rate of dilapidation of its dwelling houses, and if this goes unabated, the government will lose even more in terms of the expenditure on maintenance and repair, and eventually the houses themselves, thereby losing a good asset base. The research considers the possible causes of the rapid rate of dilapidation of the Lesotho government dwelling houses. It draws attention to the level of effectiveness of the property management structure and or framework of the Lesotho government. Further it considers the possible overall effects of the current continued dilapidation on the management of the property assets by the Lesotho government. The research draws attention to the present system of property management practiced by the government, and compares it with that of the private sector, considers the ways in which the government may have to adapt, and suggests that while the government dwelling houses are neglected in terms of maintenance, there will be some countervailing opportunities for a more effective strategic use of the property asset. A number of respondents drawn from the private sector, two government departments, and the housing occupants, were interviewed using administered and self-administered questionnaires for this research. The hypotheses ‘that efficient property asset management is significantly dependent on a good property management framework/structure’ and ‘that there is a correlation between the declining property values and the level of rentals payable to the Lesotho government’ were confirmed. This is seen in the fact that the Lesotho property management structure lacks the capacity to manage their pool of available housing structure. Moreover, that the kind of expertise available is not fitting to be able to manage the government houses. The Lesotho government lacks the required expertise for the management of its housing assets, and this has led to a rapid dilapidation of the housing stock for the inadequacy in management resulted in poor maintenance of the housing stock, as the management failed to identify key issues in property management. 3 Keywords: Property Dilapidation, Maintenance, Dwelling houses, Government Property Management.
Student Number : 0210329K - MSc research report - School of Construction Economics and Management - Faculty of Engineering and the Built Environment
Keywords: property dilapidation; maintenance; dwelling houses; government property management